El comercio de libros entre Europa y América en la Sevilla del siglo XVI: Impresores, libreros y mercaderes. - Sánchez, Carlos Alberto González (Colonial Latin American Review, 2014)
This article discusses the commercial activities involved in the book industry of Seville, Spain, during the 16th century. The author comments on the role of publishers, librarians, and merchants in forming a successful trade network with Europe and the Americas. The process of business negotiation at the time is also explored.